Три новых вида комаров-лимониид (Diptera, Limoniidae) из СССР - Савченко, Е.Н. (Вестник зоологии, 1981)
The limoniid-flies Helius gibbifer, sp. n. (Chita Region), Rhypholophus imitator, sp. n. (Khabarovsk Territory) and Antocha (s. str.) biacus, sp. n. (Tajik SSR) are described and their male genitalia are figured. The type-specimens of all these new species are preserved in the collection of the Institute of Zoology, Ukr. SSR Academy of Sciences (Kiev).